The ironic effect of deliberation: what we can (and cannot) expect in deeply divided societies (2020)
One of the foundational promises of deliberation in contemporary democracies was the transformation of citizen’s preferences by the force of the better arguments. However, deliberation has proved so far to be ineffective to promote intergroup changes for the better in terms of attitudes. As a result, evidence shows that even discussions lying relatively close to the theoretical ideal might nevertheless push changes in either a positive or a negative direction. We argue that deliberation lacks the necessary built-in mechanisms for constraining polarization and unleashing desired changes, particularly in deeply divided societies. Thus, efforts aimed at bridging the divides between adversarial groups require the promotion of specific, empathy-generating discursive contents, which even highly deliberative debate cannot ensure. Based on two experimental studies, we show how deliberation and intergroup reconciliation operate through different mechanisms. While there is no reason to believe they are incompatible, it remains to be seen how they can be set in motion simultaneously. © 2018, Springer Nature Limited.